Purification of Generator Waste Oil by Solvent Extraction - Taghreed M. Hameed; Muna M. Khudhair; Enase Jabar; Aqeel Talip; Hayder Abd Alameer (Journal of Madenat Alelem University College, 2016)
Use lubricant oil is one of the most important sources of pollution in the environment because of the massive amounts and toxicity of the compounds found in it. Therefore, purification and recycling of these oils have economic benefits as well as environmental benefits. Solvent extraction method was adopted in removal contaminants found in used lubricant oils in order to ease and affordability. Different solvents such as 1 - butanol, methyl ethyl ketone, and hexane were used to study the extraction of base oil from used lubricating oil. The extraction efficiency was evaluated by measuring the ash content in the oil output after evaporating the solvent. It was found that 1 - butanol is best suited to remove contaminants and then the methyl ethyl ketone and finally hexane. Because of close value of ash content of oil resulting from treatment with the methyl ethyl ketone to 1 - butanol , methyl ethyl ketone was used because of low cost, speed evaporation ,and easily retrieved. The optimal conditions for extraction was studied which include solvent to oil ratio, temperature and time of extraction .It has been found that the best ratio is 4.7 to 1 of the solvent from the oil at temperature 50 ° C for 30 minutes. The physical properties of treated oil were examined which include specific gravity, viscosity, pour point , flash point , ash content and total acid number and were compared with the properties of the fresh and used oil and with base oils.